Saccharomyces cerevisiae CNCM I-3856 in irritable bowel syndrome: An individual subject meta-analysis - Cayzeele-Decherf, Amélie; Pélerin, Fanny; Leuillet, Sébastien; Douillard, Benoit; Housez, Béatrice; Cazaubiel, Murielle; Jacobson, Gunnard K; Jüsten, Peter; Desreumaux, Pierre (World journal of gastroenterology : WJG, 2017)
AIM To confirm previous conclusions on Saccharomyces cerevisiae(S. cerevisiae) CNCM I-3856 for irritable bowel syndrome(IBS) management.METHODS An individual patient data meta-analysis was performed on two randomized clinical trials studying the effect of S. cerevisiae CNCM I-3856 supplementation on gastrointestinal(GI) symptoms in IBS subjects. A total of 579 IBS subjects were included. Outcomes were the daily Likert scale scores of abdominal pain/discomfort and bloating [area under the curve(AUC) and weekly means], responder status, and bowel movements(stool frequency and consistency). Statistical analyses were conducted in Intent to Treat(ITT) population, IBS-C subjects and IBS-C subjects with an abdominal pain/discomfort score higher than or equal to 2 at baseline('IBS-C ≥ 2 subpopulation').RESULTS S. cerevisiae CNCM I-3856 significantly improved abdominal pain/discomfort and bloating during the second month of supplementation [AUC(W5-W8)]with improvement up to the minimal clinically relevant threshold of 10%: a 12.3% reduction of abdominal pain/discomfort in the ITT population compared to the Placebo group(P = 0.0134) has been observed. In the IBS-C ≥ 2 subpopulation, there were a 13.1% reduction of abdominal pain/discomfort and a 14.9% reduction of bloating compared to the Placebo group(P = 0.0194 and P = 0.0145, respectively). GI symptoms significantly decreased during supplementation but no statistical differences were reported between groups at the end of the supplementation period. Responder status was defined as a subject who experienced a decrease of 1 arbitrary unit(a.u.) or 50% of the abdominal discomfort score from baseline for at least 2 wk out of the last 4 wk of the study. A significant difference between groups was reported in the ITT population, when considering the first definition: subjects in the Active group had 1.510 higher odds to be a responder(reduction of 1 a.u. of abdominal pain/discomfort) compared with subjects in the Placebo group(P = 0.0240). At the end of supplementation period, stool consistency in the Active group of the ITT population was significantly improved and classified as 'normal' compared to Placebo(respectively 3.13 ± 1.197 a.u. vs 2.58 ± 1.020 a.u., P = 0.0003). Similar results were seen in the IBS-C ≥ 2 subpopulation(Active group: 3.14 ± 1.219 a.u. vs Placebo group: 2.59 ± 1.017 a.u., P = 0.0009).CONCLUSION This meta-analysis supports previous data linking S. cerevisiae I-3856 and improvement of GI symptoms, in IBS overall population and in the IBS-C and IBS-C ≥ 2 subpopulations.